Polyethyleneimine grafted sulfur modified lignin catching agent as well as preparation method and application thereof
By grafting lignin with sulfur modification and polyethyleneimine graft copolymerization, a polyethyleneimine grafted sulfur modified lignin capture agent with high capture performance and structural stability was prepared, and the existing lignin capture agent was solved. The problems of low capture performance and poor stability are achieved, and efficient removal of heavy metals is achieved.
Patent Information
- Application Number
- CN202411601541.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
Existing lignin capture agents show problems of low capture performance and poor structural stability in capturing heavy metals.
By modifying lignin with sulfonic acid, xanthan acid or thiol group, initial sulfur-modified lignin is formed, and then graft copolymerization is used to prepare polyethyleneimine graft sulfur-modified lignin Capture agent.
The structural stability of the capture agent and the capture performance of heavy metals are improved, and efficient green management of heavy metals in wastewater is achieved.
Smart Images

Figure CN119463196A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy metal pollution control, and in particular relates to a polyethyleneimine grafted sulfur-modified lignin scavenger and a preparation method and application thereof. Background Art
[0002] Modern industry is developing rapidly. At the same time, each process of industrial production will discharge a large amount of heavy metal wastewater. Heavy metals are highly toxic and non-degradable. They are easy to migrate and accumulate in the ecosystem. Even at very low concentrations, they can pose a threat to human life and safety. Commonly used methods for treating heavy metals in wastewater include membrane filtration, chemical precipitation, bioremediation, electrochemical and adsorption methods, etc. These methods each have their own advantages and disadvantages. The capture method is currently recognized as an effective and economical method for treating heavy metal wastewater. Through mass transfer between liquid and solid, heavy metal ions are transferred from wastewater to the surface of the capture agent. Through physical effects such as van der Waals force between the capture agent and chemical effects such as ion exchange or electrostatic attraction, the purpose of separating heavy metals from wastewater is achieved.
[0003] The application of the capture method focuses on the selection and preparation of capture agent materials. Generally speaking, an ideal capture agent should have the advantages of high efficiency, stability, low cost, and environmental protection. Lignin has been widely studied in the treatment of different types of water pollutants due to its low cost, abundant sources, biocompatibility, and wide distribution of active sites. Lignin is abundant and widely present in cellulose. The lignin structural unit is composed of benzene rings and side chains, including active groups such as phenolic hydroxyl, alcoholic hydroxyl, carboxyl, and methoxy. Carboxyl and hydroxyl groups have strong hydrophilicity and complexation with metal ions, but single lignin capture agents have problems such as low capture performance and poor structural stability. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation method and application of a polyethyleneimine grafted sulfur-modified lignin scavenger. The preparation process of the scavenger of the present invention is simple and low in cost, and it can treat heavy metal pollution in wastewater in a green and efficient manner, providing favorable guarantees for improving industrial wastewater treatment problems and achieving green economic development.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A method for preparing a polyethyleneimine grafted sulfur-modified lignin scavenger comprises the following steps: firstly modifying lignin with sulfonic acid group, xanthate group or mercapto group to obtain preliminary sulfur-modified lignin; then grafting and copolymerizing the preliminary sulfur-modified lignin with polyethyleneimine to obtain the polyethyleneimine grafted sulfur-modified lignin scavenger.
[0008] Since the present invention firstly modifies lignin with sulfonic acid groups, xanthogenic acid groups or mercapto groups to obtain preliminary sulfur-modified lignin, the preliminary sulfur-modified lignin is substantially sulfonic acid-modified lignin, xanthogenic acid-modified lignin or mercapto-modified lignin. For example, when lignin is modified with sulfonic acid groups, the preliminary sulfur-modified lignin obtained is sulfonic acid-modified lignin.
[0009] Preferably, the method for modifying lignin using sulfonic acid groups is as follows:
[0010] The lignin, water, ferrous sulfate and hydrogen peroxide are mixed and reacted in a water bath, and formaldehyde and sodium sulfonate are added to continue the reaction. After the reaction is completed, the mixture is cooled and centrifuged, and the precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
[0011] Preferably, in the method of modifying lignin with sulfonic acid groups to obtain preliminary sulfur-modified lignin, the mass ratio of the lignin to the ferrous sulfate is 10:1;
[0012] The mass ratio of the sodium sulfonate to the lignin is 3:10;
[0013] The temperature of the water bath was 80°C.
[0014] Preferably, in the method of modifying lignin with sulfonic acid groups to obtain preliminary sulfur-modified lignin, the mass fraction of hydrogen peroxide is 30%.
[0015] Preferably, in the method of modifying lignin with sulfonic acid groups to obtain preliminary sulfur-modified lignin, the centrifugal speed is 8000 r / min and the centrifugal time is 10 min.
[0016] More preferably, the lignin is modified by sulfonic acid groups, and the obtained preliminary sulfur-modified lignin is recorded as sulfonic acid-modified lignin, which is prepared by Fenton oxidation method, and the specific method is:
[0017] Add 2g of alkali lignin, 70mL of deionized water, 0.2g of ferrous sulfate and 1.2mL of 30% (mass fraction) hydrogen peroxide into a three-necked flask, place it in a water bath, control the temperature at 80°C, and mechanically stir at 400r / min for 2h. Add 0.75mL of formaldehyde and 0.6g of sodium sulfonate, and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge at 8000r / min for 10min in a centrifuge, wash the lower precipitate with distilled water until neutral, vacuum dry and mechanically grind to obtain sulfonic acid modified lignin.
[0018] Preferably, the method for modifying lignin using xanthate is as follows:
[0019] The lignin is dissolved in water, the pH is adjusted to alkaline, formaldehyde is added after stirring evenly, and the reaction is carried out in a water bath, sodium hydroxide and carbon disulfide are added, and the reaction is continued. After the reaction is completed, the reaction is cooled, hydrochloric acid is added, and the reaction is allowed to stand and then centrifuged. The precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
[0020] Preferably, in the method of modifying lignin with xanthate to obtain preliminary sulfur-modified lignin, the mass ratio of lignin, sodium hydroxide and carbon disulfide is 1:1:5;
[0021] The temperature of the water bath is 90°C;
[0022] Before adding sodium hydroxide and carbon disulfide, the temperature of the water bath was reduced to 40°C.
[0023] Preferably, in the method for modifying lignin with xanthate to obtain preliminary sulfur-modified lignin, the step of adjusting the pH to alkaline is adjusting the pH to 13.
[0024] Preferably, in the method of modifying lignin with xanthate to obtain preliminary sulfur-modified lignin, the hydrochloric acid is a hydrochloric acid solution with a concentration of 6 mol / L.
[0025] Preferably, in the method of modifying lignin with xanthate to obtain preliminary sulfur-modified lignin, the centrifugal speed is 8000 r / min and the centrifugal time is 10 min.
[0026] More preferably, the lignin is modified by xanthate, and the obtained preliminary sulfur-modified lignin is recorded as xanthate-modified lignin, which is prepared by formaldehyde methylation method, and the specific method is:
[0027] Take 2g of lignin and dissolve it in 75mL of deionized water. Adjust the pH to 13 with 2mol / L sodium hydroxide solution, use a magnetic stirrer to control the speed of 200r / min to stir evenly, add 10mL of formaldehyde, react for 30min, pour into a three-necked flask, place it in a water bath, control the temperature at 90℃, and stir mechanically at 400r / min. When the reaction is 3h, the temperature is adjusted to 40℃, 2g of sodium hydroxide and 10g of carbon disulfide are added, and the reaction is continued for 2h. After the reaction is completed and cooled, 5mL of 6mol / L hydrochloric acid is added, and it is allowed to stand for 2h. After the reaction is completed, centrifuge at 8000r / min for 10min, wash the lower precipitate with distilled water until it is neutral, vacuum dry and mechanically grind to obtain xanthogenic acid modified lignin.
[0028] Preferably, the method of modifying lignin by using mercapto groups to obtain preliminary sulfur-modified lignin is as follows:
[0029] The lignin, N-acetyl-L-cysteine and N,N-dimethylformamide are dissolved in dioxane, irradiated with ultraviolet light, centrifuged, and the precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
[0030] Preferably, in the method of modifying lignin with thiol to obtain preliminary sulfur-modified lignin, the mass ratio of lignin, N-acetyl-L-cysteine and N,N-dimethylformamide is 4:37:1.2.
[0031] Preferably, in the method of modifying lignin with thiol to obtain preliminary sulfur-modified lignin, the ultraviolet irradiation is irradiation with an ultraviolet lamp, more preferably irradiation with a 365nm ultraviolet lamp for 12 hours.
[0032] Preferably, in the method of modifying lignin with mercapto groups to obtain preliminary sulfur-modified lignin, the centrifugal speed is 8000 r / min and the centrifugal time is 10 min.
[0033] More preferably, the lignin is modified by mercapto groups, and the obtained preliminary sulfur-modified lignin is recorded as mercapto-modified lignin, which is prepared by an ultraviolet initiation method, and the specific method is:
[0034] 0.4 g of lignin, 3.7 g of N-acetyl-L-cysteine and 0.12 g of N,N-dimethylformamide were dissolved in 20 mL of dioxane to obtain a mixed solution, which was irradiated under 365 nm ultraviolet light for 12 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, and the lower precipitate was washed with ethanol and distilled water, vacuum dried and mechanically ground to obtain thiol-modified lignin.
[0035] Preferably, the method of graft copolymerizing the preliminary sulfur-modified lignin using polyethyleneimine is as follows:
[0036] The preliminary sulfur-modified lignin, polyethyleneimine and water are mixed, stirred evenly in a water bath, formaldehyde is added, reacted at a constant temperature, cooled after the reaction is completed, the pH is adjusted to acidic, centrifuged, and the precipitate is washed and dried to obtain the polyethyleneimine grafted sulfur-modified lignin capture agent.
[0037] Preferably, in the method of graft copolymerizing the preliminary sulfur-modified lignin using polyethyleneimine, the mass ratio of the preliminary sulfur-modified lignin to polyethyleneimine is 1:2;
[0038] The temperature of the water bath is 60°C;
[0039] The step of adjusting the pH to acidic is adjusting the pH to 6.
[0040] More preferably, the method of graft copolymerizing the preliminary sulfur-modified lignin with polyethyleneimine is:
[0041] (1) 0.5 g of preliminary sulfur-modified lignin, 1 g of polyethyleneimine and 40 mL of deionized water were mixed in a three-necked flask, placed in a water bath, the temperature was controlled at 60 ° C, and mechanically stirred at 400 r / min to obtain a mixed solution;
[0042] (2) adding 1 g of formaldehyde to the mixed solution of step (1), reacting at a constant temperature for 5 h, and cooling to room temperature after the reaction;
[0043] (3) The mixture obtained in step (2) was adjusted to pH 6 using 1 mol / L hydrochloric acid, and centrifuged at 8000 r / min for 10 min. The lower precipitate was washed three times with distilled water, freeze-dried at -60°C, and ground to obtain a polyethyleneimine grafted sulfur-modified lignin scavenger.
[0044] Preferably, in the method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger, the lignin is alkali lignin.
[0045] Preferably, the preliminary sulfur-modified lignin is sulfonic acid-modified lignin.
[0046] Sulfur-containing functional groups generally include sulfonic acid groups, mercapto groups, xanthate groups, etc., which have a strong affinity for heavy metals. However, different functional groups bind to lignin in different ways, and the modification methods and conditions have great differences in affinity for heavy metals. Polyethyleneimine is an active macromolecule with abundant active groups. Branched polyethyleneimine exists in liquid state at room temperature. It is a water-soluble high molecular polymer. The molecular chain contains a large number of amino functional groups, which can improve the stability of the material structure. Therefore, the present invention first modifies lignin with sulfonic acid groups, mercapto groups or xanthate groups, and then grafts polyethyleneimine to obtain a capture agent that is stable, contains bifunctional functional groups of sulfur and amino groups, and has a strong affinity for heavy metals.
[0047] The second technical solution of the present invention:
[0048] The present invention also provides a polyethyleneimine grafted sulfur-modified lignin capture agent prepared according to the method.
[0049] The polyethyleneimine grafted sulfur-modified lignin scavenger prepared by the present invention has the characteristics of large specific surface area, wide pore size distribution, rich surface functional groups, etc., and can achieve effective capture and rapid removal of heavy metals in wastewater. The sulfonic acid, xanthogenic acid, thiol and amino groups introduced by sulfur modification and polyethyleneimine grafting can undergo complexation with lead and cadmium ions to form coordination bonds, thereby strengthening the affinity of the functional groups of lignin itself for lead and cadmium ions; the hydroxyl groups in the lignin structure are protonated in a weakly acidic environment, and can undergo cation exchange with lead and cadmium ions, further enhancing the removal effect of heavy metal ions.
[0050] The third technical solution of the present invention:
[0051] The present invention also provides application of the polyethyleneimine grafted sulfur-modified lignin capture agent in treating heavy metal pollution in wastewater.
[0052] When the polyethyleneimine grafted sulfur-modified lignin scavenger of the present invention is used to treat heavy metal pollution in wastewater, the method is as follows: adding the polyethyleneimine grafted sulfur-modified lignin scavenger to the wastewater to be treated, the addition amount of the polyethyleneimine grafted sulfur-modified lignin scavenger is 0.5-0.7g / L, and reacting at 20-30°C for 1-3h.
[0053] Preferably, when the polyethyleneimine grafted sulfur-modified lignin scavenger is used to treat heavy metal pollution in wastewater, the dosage of the polyethyleneimine grafted sulfur-modified lignin scavenger is 0.6 g / L, the reaction temperature is 25° C., the reaction time is 2 h, and the pH is 6.
[0054] Preferably, the heavy metal is at least one of lead, cadmium and nickel.
[0055] Compared with the prior art, the present invention has the following advantages and technical effects:
[0056] (1) Sulfur-containing functional group-modified lignin enhances the hydrophilicity of lignin and effectively improves its heavy metal capture performance. The present invention comprehensively compares the structural properties and heavy metal ion capture performance of three sulfur-containing functional group-modified lignins, namely, sulfonic acid group, xanthate group, and mercapto group, and finds that sulfonic acid group-modified lignin has the best heavy metal ion capture performance.
[0057] (2) Polyethyleneimine grafted sulfur modified lignin significantly improved the structural stability of lignin, solved the problem of surface cracks, and greatly improved the capture performance of heavy metal ions.
[0058] (3) The use of dual-functional group modified lignin capture agents overcomes the shortcomings of single lignin, effectively combines physical adsorption and chemical action, and achieves efficient and green treatment of heavy metals in wastewater, with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0060] Figure 1 Thermogravimetric analysis of three sulfur-containing functional group-modified lignins in Examples 1 to 3 and their capture effects on lead and cadmium, (a) is a thermogravimetric graph, (b) is a thermogravimetric rate graph, and (c) is a lead / cadmium capture effect graph;
[0061] Figure 2 The surface morphology and surface functional group distribution of the polyethyleneimine grafted sulfur-modified lignin scavenger in Example 1, (a) is a 5 μm surface morphology image (scanning electron microscope image), (b) is a 3 μm surface morphology image, (c) is a 2 μm surface morphology image, (d) is an infrared spectrum (FT-IR) image before and after PEI grafting (wherein the sulfonic acid-modified lignin is before PEI grafting, and the PEI-grafted sulfonic acid-modified lignin is after PEI grafting);
[0062] Figure 3 The capture performance of the polyethyleneimine grafted sulfur-modified lignin capture agent for lead and cadmium in Example 1 at different initial concentrations, (a) is the effect of the initial concentration of lead on the lead capture effect, and (b) is the effect of the initial concentration of cadmium on the cadmium capture effect;
[0063] Figure 4 The capture performance of the polyethyleneimine grafted sulfur-modified lignin capture agent for lead and cadmium after five cycles in Example 1, (a) is the effect of the number of cycles on the capture effect of lead, and (b) is the effect of the number of cycles on the capture effect of cadmium;
[0064] Figure 5 The thermogravimetric analysis diagram of the sulfur-modified lignin-based capture agent before and after polyethyleneimine modification in Example 1, (a) is the mass change at different temperatures, and (b) is the thermal weight loss rate at different temperatures. DETAILED DESCRIPTION
[0065] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0066] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0067] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0068] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0069] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0070] In the present invention, unless otherwise specified, room temperature is 25±2°C.
[0071] In the present invention, the terms "sulfur-modified lignin" and "three types of sulfur-containing functional group-modified lignin" all refer to one of sulfonic acid-modified lignin, xanthogenic acid-modified lignin and mercapto-modified lignin.
[0072] All raw materials used in the embodiments of the present invention are purchased from commercial sources. For example, alkali lignin is purchased from Aladdin Biochemical Technology Co., Ltd.; polyethyleneimine is purchased from Aladdin Biochemical Technology Co., Ltd.
[0073] The technical solution of the present invention is further illustrated by the following embodiments.
[0074] Example 1
[0075] (1) Add 2 g of alkali lignin, 70 mL of deionized water, 0.2 g of ferrous sulfate and 1.2 mL of 30% (mass fraction) hydrogen peroxide to a three-necked flask, place it in a water bath, control the temperature at 80°C, and mechanically stir at 400 r / min for 2 h. Add 0.75 mL of formaldehyde and 0.6 g of sodium sulfonate, and continue the reaction for 2 h. After the reaction is completed, cool to room temperature and centrifuge at 8000 r / min for 10 min in a centrifuge. Wash the lower precipitate with distilled water until it is neutral, vacuum dry and mechanically grind to obtain sulfonic acid-modified lignin;
[0076] (2) 0.5 g of sulfonic acid-modified lignin, 1 g of polyethyleneimine and 40 mL of deionized water were mixed in a three-necked flask, placed in a water bath, the temperature was controlled at 60 ° C, and mechanically stirred at 400 r / min to obtain a mixed solution;
[0077] (3) adding 1 g of formaldehyde to the mixed solution of step (1), reacting at a constant temperature for 5 h, and cooling to room temperature after the reaction;
[0078] (4) The mixture obtained in step (2) was adjusted to pH 6 using 1 mol / L hydrochloric acid solution, and centrifuged at 8000 r / min for 10 min. The lower precipitate was washed three times with distilled water, freeze-dried at -60°C, and ground to obtain a polyethyleneimine grafted sulfur-modified lignin scavenger (PEI grafted sulfonic acid-modified lignin).
[0079] The specific surface area, pore size and pore volume distribution of the sulfur-modified lignin before and after polyethyleneimine modification in Example 1 are shown in Table 1.
[0080] Table 1 Specific surface area and pore size distribution of sulfur-modified lignin before and after polyethyleneimine modification in Example 1
[0081]
[0082] As shown in Table 1, the specific surface areas of the sulfonic acid modified lignin scavengers are 2.559 m 2 / g, the average pore diameter is 1.409nm, and the specific surface area of the lignin capture agent after PEI grafting is 4.326m 2 / g, and the average pore size is 5.869nm, respectively, which significantly increases the specific surface area and pore size. The increase in the specific surface area and pore size of the material is conducive to the attachment of lead / cadmium ions, increases the contact with lead / cadmium ions, and greatly improves the capture efficiency of lead / cadmium ions. In short, the polyethyleneimine grafted sulfur-modified lignin capture agent prepared by the present invention has the characteristics of large specific surface area and wide pore size distribution.
[0083] Example 2
[0084] (1) Take 2g of alkaline lignin and dissolve it in 75mL of deionized water, adjust the pH to 13 with 2mol / L sodium hydroxide solution, use a magnetic stirrer to control the speed of 200r / min to stir evenly, add 10mL of formaldehyde, react for 30min, pour into a three-necked flask, place in a water bath, control the temperature at 90℃, and stir mechanically at 400r / min. After reacting for 3h, adjust the temperature to 40℃, add 2g of sodium hydroxide and 10g of carbon disulfide, and continue to react for 2h. After the reaction is completed and cooled, add 5mL of 6mol / L hydrochloric acid solution, let it stand for 2h, and centrifuge at 8000r / min for 10min after the end. Wash the lower precipitate with distilled water until it is neutral, vacuum dry and mechanically grind to obtain xanthogenic acid modified lignin;
[0085] (2) 0.5 g of xanthogenic acid-modified lignin, 1 g of polyethyleneimine and 40 mL of deionized water were mixed in a three-necked flask, placed in a water bath, the temperature was controlled at 60 ° C, and mechanically stirred at 400 r / min to obtain a mixed solution;
[0086] (3) adding 1 g of formaldehyde to the mixed solution of step (1), reacting at a constant temperature for 5 h, and cooling to room temperature after the reaction;
[0087] (4) The mixture obtained in step (2) was adjusted to pH 6 using 1 mol / L hydrochloric acid, and centrifuged at 8000 r / min for 10 min. The lower precipitate was washed three times with distilled water, freeze-dried at -60°C, and ground to obtain a polyethyleneimine grafted xanthogenic acid modified lignin scavenger.
[0088] Example 3
[0089] (1) 0.4 g of alkali lignin, 3.7 g of N-acetyl-L-cysteine and 0.12 g of N,N-dimethylformamide were dissolved in 20 mL of dioxane to obtain a mixed solution, and the mixed solution was placed under 365 nm ultraviolet light for 12 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, and the lower precipitate was washed with ethanol and distilled water, vacuum dried and mechanically ground to obtain thiol-modified lignin;
[0090] (2) 0.5 g of thiol-modified lignin, 1 g of polyethyleneimine and 40 mL of deionized water were mixed in a three-necked flask, placed in a water bath, the temperature was controlled at 60 ° C, and mechanically stirred at 400 r / min to obtain a mixed solution;
[0091] (3) adding 1 g of formaldehyde to the mixed solution of step (1), reacting at a constant temperature for 5 h, and cooling to room temperature after the reaction;
[0092] (4) The mixture obtained in step (2) was adjusted to pH 6 using 1 mol / L hydrochloric acid solution, and centrifuged at 8000 r / min for 10 min. The lower precipitate was washed three times with distilled water, freeze-dried at -60°C, and ground to obtain a polyethyleneimine grafted thiol-modified lignin scavenger.
[0093] Effect Example 1 Structural Characterization of Sulfur-modified Lignin and Capture of Lead and Cadmium
[0094] The specific steps include:
[0095] 8 g of the prepared sulfur-modified lignin (i.e., the three modified lignin scavengers prepared in Examples 1 to 3) were placed in a ceramic crucible and heated at N 2 The thermal stability was tested by LABSYS EVO thermogravimetric analyzer at a rate of 20°C / min from 30°C to 800°C under a temperature-dependent manner.
[0096] In a 100 mL conical flask, 20 mL of 300 mg / L Pb(II) solution and Cd(II) solution were added respectively, and the dosage of sulfur-modified lignin capture material was set to 4 g / L. It was placed on an oscillator at 25 °C and 180 rpm for 2 hours. After the reaction, it was transferred to a 50 mL centrifuge tube and centrifuged at 8000 r / min for 10 minutes. The supernatant was filtered through a 0.22 μm filter membrane, and then the filtrate was diluted and the residual Pb(II) and Cd(II) concentrations were determined using an atomic absorption spectrometer.
[0097] Figure 1 The thermogravimetric analysis of the three sulfur-containing functional group-modified lignins in Examples 1 to 3 and the capture effect diagrams of lead and cadmium. It can be seen that after the xanthogenic acid group and the thiol group modified lignin, the functional group was connected to the lignin structure through chemical reaction, resulting in a decrease in its thermal stability. Compared with the other two functional group modifications, the sulfonic acid group-modified lignin has a better thermal stability and basically no decomposition of the material structure under high temperature conditions.
[0098] From the capture effect diagram of lead and cadmium ions by sulfur-modified lignin, it can be seen that when the initial concentrations of lead and cadmium ions are both 300 mg / L, the dosage of lignin capture agent is 4.0 g / L, and the reaction time is 2 h, the three types of sulfur-containing functional group-modified lignin have a high removal effect on lead ions, with removal rates between 80% and 95%. Among them, the sulfonic acid group-modified lignin capture agent has the best removal effect on lead ions. At the same initial concentration, the cadmium ion removal rate is lower than that of the lead ion because the cadmium ion reaches adsorption saturation.
[0099] Effect Example 2 Characterization of Polyethyleneimine Grafted Sulfur Modified Lignin Capture Agent
[0100] Take 0.01g of the dried polyethyleneimine grafted sulfur-modified lignin scavenger prepared in Example 1 and stick it on the base with a conductive double-sided tape, spray gold with an ion sputtering coating machine, fix it on a circular sample stage, and put the sample stage into a scanning electron microscope for observation. Adjust the appropriate brightness and contrast, adjust the appropriate magnification, and adjust the focal length to present a clear image.
[0101] 0.1 g of the sample (i.e., the polyethyleneimine grafted sulfur-modified lignin scavenger prepared in Example 1) was mixed with potassium bromide at a mass ratio of 1:100, ground into powder, and pressed into a tablet. The tablet was placed in the groove of a Fourier transform infrared spectrometer for testing, with a scanning range of 500-4000 cm -1 , scanned 32 times, with a resolution of 4.
[0102] Figure 2The surface morphology and surface functional group distribution of the polyethyleneimine grafted sulfur-modified lignin scavenger in Example 1. It can be seen from the scanning electron microscope image that the polyethyleneimine cross-linked scavenger makes up for the cracks that appear in the sulfur-modified lignin scavenger, presenting a stacked porous shell. The pore structure in the polyethyleneimine shell is formed by the cross-linking of polyethyleneimine and sulfur-modified lignin. The porous shell not only enhances the mechanical stability of the material, but also provides sufficient "binding sites" for metal ions, promoting the effective mass transfer of metal ions in its sufficient interstitial space. In addition, the cross-linking effect of polyethyleneimine makes the scavenger particles more uniform. As can be seen from the FT-IR image, 3407cm -1 The peak at 1658cm-1 was red-shifted, indicating that the stretching vibration peak of NH in polyethyleneimine overlapped with the original -OH stretching vibration peak. -1 and 1327cm -1 -NH appears 2 and weaker -CN characteristic peaks, indicating that amine functional groups were successfully introduced after polyethyleneimine grafting.
[0103] Effect Example 3 Effect of different initial conditions on the capture of lead and cadmium by polyethyleneimine grafted sulfur-modified lignin capture agent
[0104] Take 20mL of lead and cadmium solutions, and set the initial Pb(II) concentration to 300mg / L, 500mg / L, 800mg / L, 1000mg / L and 2000mg / L; the initial Cd(II) concentration to 100mg / L, 200mg / L, 300mg / L, 400mg / L and 500mg / L;
[0105] The dosage of the polyethyleneimine grafted sulfur-modified lignin scavenger in Example 1 was set to 0.6 g / L, the solution pH was 6, the reaction time was 2 h, and the mixture was placed on an oscillator at 25° C. and 180 rpm to conduct an experiment on the capture of lead and cadmium by the polyethyleneimine grafted sulfur-modified lignin scavenger;
[0106] After the reaction, it was transferred to a 50 mL centrifuge tube and centrifuged at 8000 r / min for 10 min. The supernatant was filtered through a 0.22 μm filter membrane, and then the filtrate was diluted and the residual Pb (II) and Cd (II) concentrations were determined using an atomic absorption spectrometer.
[0107] Figure 3The results of the effects of different initial conditions on the capture of lead and cadmium by the polyethyleneimine grafted sulfur-modified lignin capture agent in Example 1 show that with the increase of the initial concentration of lead / cadmium ions, the removal capacity of the capture agent for Pb(II) / Cd(II) increases, indicating that the higher lead / cadmium ion concentration increases the driving force to overcome the mass transfer resistance barrier between the solid phase and the aqueous phase. However, when the lead / cadmium ion concentration is too high, the removal capacity for Pb(II) / Cd(II) tends to balance, because the rapid increase in the concentration of metal cations causes the material binding sites to reach adsorption saturation, and shields the negative charge on the surface of some capture agents, causing the material molecular chains to curl up and agglomerate, thereby causing some functional groups in the capture agent, such as carboxyl, amino, hydroxyl, etc., to be wrapped inside and unable to fully and effectively bind to Pb(II) / Cd(II). When the initial concentration of Pb(II) was 500 mg / L, the Pb(II) capture capacity was 368.55 mg / g, and when the initial concentration of Cd(II) was 300 mg / L, the Cd(II) capture capacity was 322.63 mg / g.
[0108] Effect Example 4 Polyethyleneimine grafted sulfur-modified lignin capture agent for lead and cadmium cyclic capture
[0109] (1) The dosage of the polyethyleneimine grafted sulfur-modified lignin scavenger in Example 1 was controlled to be 0.6 g / L, the pH was 6, the reaction time was 30 min, the initial concentration of Pb(II) was 500 mg / L, and the initial concentration of Cd(II) was 300 mg / L, and lead and cadmium ions were captured. After the reaction, the mixture was centrifuged at 8000 r / min for 10 min, and the supernatant was filtered with a 0.22 μm filter head. The residual Pb(II) / Cd(II) content was determined by an atomic absorption spectrometer, and the removal rate and capture capacity were calculated. This step was recorded as the 0th cycle.
[0110] (2) The lower precipitate after centrifugation in step (1) was added to 50 mL of 0.1 mol / L nitric acid solution, and reacted on an oscillator at 180 rpm for 4 h to perform an analytical experiment.
[0111] (3) The mixed solution after the reaction in step (2) was centrifuged at 8000 r / min for 10 min, and washed with distilled water until the supernatant was neutral. The same capture process was performed here, and this process was recorded as one cycle. The same operation was performed for 5 cycles.
[0112] Figure 4The results of the effect of five cycles of the polyethyleneimine grafted sulfur-modified lignin scavenger on the capture performance of lead and cadmium in Example 1 show that after five cycles, the removal effect of lead / cadmium ions gradually decreases, but still has a high removal capacity. In the fifth cycle, the removal capacity of lead ions is 314.23 mg / g, and the removal capacity of cadmium ions is 242.58 mg / g. After five cycles, the capture rates of lead and cadmium remain at 81.8% and 75.2%, respectively, indicating that the polyethyleneimine grafted sulfur-modified lignin scavenger has good reusability.
[0113] Effect Example 5 Thermal Stability of Polyethyleneimine Grafted Sulfur-Modified Lignin Capture Agent
[0114] 8 g of the prepared sulfur-modified lignin and polyethyleneimine-grafted sulfur-modified lignin were placed in a ceramic crucible and heated under N 2 The thermal stability was tested by LABSYS EVO thermogravimetric analyzer at a rate of 20°C / min from 30°C to 800°C under a temperature-dependent manner.
[0115] Figure 5 The thermogravimetric analysis diagram of the sulfur-modified lignin-based scavenger before and after polyethyleneimine modification in Example 1. The mass loss at 100°C is mainly the result of the evaporation of water contained in the material; and between 100-400°C, the mass loss of polyethyleneimine-grafted sulfur-modified lignin is smaller than that of the sulfur-modified lignin scavenger, indicating that the sulfur-modified lignin scavenger after polyethyleneimine grafting has better heat resistance.
[0116] Comparative Example 1
[0117] Jin et al. (Clickable Synthesis of 1,2,4-Triazole Modified LigninBased Adsorbent for the Selective Removal of Cd(II)[J]. Acs Sustainable Chemistry & Engineering, 2017, 5(5): 4086-4093) dissolved 0.5 g of alkali lignin, 1 g of 1,2,4-triazole-3-thiol and 30 mg of DMPA in 10 mL of THF solvent, then irradiated the mixture under a 365 nm UV lamp for 30 min, removed the THF solvent by rotary evaporation, and washed the crude product with excess methanol to remove unreacted thiotriazole compounds and DMPA to obtain a 1,2,4-triazole modified lignin-based adsorbent for the selective removal of Cd(II). 2+ The removal capacity is 87.4 mg / g.
[0118] In the present invention, 0.4 g of alkali lignin, 3.7 g of N-acetyl-L-cysteine and 0.12 g of N,N-dimethylformamide are dissolved in 20 mL of dioxane to obtain a mixed solution, the mixed solution is placed under 365 nm ultraviolet light for 12 hours, and after the reaction is completed, the mixture is centrifuged at a speed of 8000 r / min for 10 minutes, and the lower precipitate is washed with ethanol and distilled water, vacuum dried and mechanically ground to obtain thiol-modified lignin, and the Cd 2+ The removal capacity can reach 130.8 mg / g.
[0119] Comparative Example 2
[0120] Li et al. (Preparation of PEI / CS aerogel beads with a high density of reactive sites for efficient Cr(VI)sorption: batch and column studies[J]. RscAdvances, 2017, 7(64): 40227-40236) poured 10g of alkaline lignin and 100mL of distilled water into a three-necked round-bottom flask, heated to 80°C, and adjusted the pH to 12 with NaOH. 10mL of formaldehyde was dripped into the flask for 3h of hydroxymethylation reaction. After the reaction was completed, the mixture was cooled to 30°C. 4g of NaOH was added, and 10mL of carbon sulfide was dripped in. After reacting at 30°C for 2h, it was precipitated with 0.1M HCl at pH 3 and filtered, washed with distilled water until neutral, vacuum dried and ground to obtain a xanthogenic acid-modified lignin scavenger for Pb 2+ The maximum adsorption capacity is 64.9 mg / g.
[0121] In the present invention, 2g of alkali lignin is dissolved in 75mL of deionized water, the pH is adjusted to 13 with a 2mol / L sodium hydroxide solution, and a magnetic stirrer is used to control the speed of 200r / min for uniform stirring, 10mL of formaldehyde is added thereto, the mixture is reacted for 30min, poured into a three-necked flask, placed in a water bath, the temperature is controlled at 90°C, and mechanical stirring is performed at 400r / min. When the reaction is completed for 3h, the temperature is adjusted to 40°C, 2g of sodium hydroxide and 10g of carbon disulfide are added, and the reaction is continued for 2h. After the reaction is completed and cooled, 5mL of 6mol / L hydrochloric acid solution is added, and the mixture is allowed to stand for 2h. After the reaction is completed, the mixture is centrifuged at a speed of 8000r / min for 10min, and the lower precipitate is washed with distilled water until it is neutral, vacuum dried, and mechanically ground to obtain xanthogenic acid-modified lignin. 2+ The maximum adsorption capacity can reach 242.4 mg / g.
[0122] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a polyethyleneimine grafted sulfur-modified lignin scavenger, characterized in that: Firstly, lignin is modified by using sulfonic acid group, xanthate group or mercapto group to obtain preliminary sulfur-modified lignin, and then polyethyleneimine is used to graft copolymerize the preliminary sulfur-modified lignin to obtain the polyethyleneimine grafted sulfur-modified lignin capture agent.
2. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 1, characterized in that: The method of modifying lignin using sulfonic acid groups is as follows: The lignin, water, ferrous sulfate and hydrogen peroxide are mixed and reacted in a water bath, and formaldehyde and sodium sulfonate are added to continue the reaction. After the reaction is completed, the mixture is cooled and centrifuged, and the precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
3. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 2, characterized in that: The mass ratio of the lignin to the ferrous sulfate is 10:1; The mass ratio of the sodium sulfonate to the lignin is 3:10; The temperature of the water bath was 80°C.
4. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 1, characterized in that: The method of modifying lignin using xanthate is as follows: The lignin is dissolved in water, the pH is adjusted to alkaline, formaldehyde is added after stirring evenly, and the reaction is carried out in a water bath, sodium hydroxide and carbon disulfide are added, and the reaction is continued. After the reaction is completed, the reaction is cooled, hydrochloric acid is added, and the reaction is allowed to stand and then centrifuged. The precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
5. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 4, characterized in that: The mass ratio of the lignin, sodium hydroxide and carbon disulfide is 1:1:5; The temperature of the water bath is 90°C; Before adding sodium hydroxide and carbon disulfide, the temperature of the water bath was reduced to 40°C.
6. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 1, characterized in that: The method of modifying lignin using thiol is as follows: The lignin, N-acetyl-L-cysteine and N,N-dimethylformamide are dissolved in dioxane, irradiated with ultraviolet light, centrifuged, and the precipitate is washed and dried to obtain the preliminary sulfur-modified lignin.
7. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 6, characterized in that: The mass ratio of the lignin, N-acetyl-L-cysteine and N,N-dimethylformamide is 4:37:1.
2.
8. The method for preparing the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 1, characterized in that: The method of graft copolymerizing the preliminary sulfur-modified lignin using polyethyleneimine is as follows: The preliminary sulfur-modified lignin, polyethyleneimine and water are mixed, stirred evenly in a water bath, formaldehyde is added, reacted at a constant temperature, cooled after the reaction is completed, the pH is adjusted to acidic, centrifuged, and the precipitate is washed and dried to obtain the polyethyleneimine grafted sulfur-modified lignin capture agent.
9. A polyethyleneimine grafted sulfur-modified lignin scavenger, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the polyethyleneimine grafted sulfur-modified lignin scavenger according to claim 9 in treating heavy metal pollution in wastewater.
Citation Information
Patent Citations
Preparation method of heavy metal ion absorbent (polyethyleneimine-sodium lignin sulfonate)
CN104624178A
Method for preparing lignin-based heavy metal ion adsorption material through sulfhydryl-alkenyl click reaction
CN107619480A
Organic-inorganic compound sewage treatment agent and preparation method thereof
CN109809519A
Inhalable antimicrobial particles and methods of making the same
WO2018226614A1
Small type ii CAS proteins and methods of use thereof
WO2021097118A1